Antimicrobial and Antioxidant Activity of the Essential Oil of the Turkish Endemic Species Achillea phrygia Boiss. & Bal - Akçin, A.; Aytaş Akçin, T.A.; Seyis, F.; Çoban, A.Y.; Durupínar, B. (Har Krishan Bhalla and Sons jeobp@rediffmail.com, 2014)
The essential oil obtained from the dried flowering aerial parts of Achillea phrygia Boiss & Bal. by hydrodistilation was analysed by gas chromotography-mass spectrometry. Camphor (35.55 %), 2- furaldehyde (16.59 %) and 1,8-cineol (eucalyptol) (10.12 %) were detected as the major components of the essential oil. Essential oil of the plant was also tested for antimicrobial activity using the disc-diffusion method against 6 reference bacterial strains and 65 clinical bacterial isolates. Essential oil of A. phrygia showed antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA), methicillin-sensitive S. aureus (MSSA), Acinetobacter baumannii and bacterial strains as S. aureus ATCC 25923, S. aureus ATCC 43300, Acinetobacter baumannii ATCC 19606. In additionally, the essential oil were not effective against bacterial strains as Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29212. Morover, the total antioxidant capacity and the scavenging effect on 2,2diphenil-1-picrylhydrazyl (DPPH) radicals of the essential oil were also evaluated. The radical scavenging activity of A. phrygia essential oil was 40.43 %. © 2014 © 2014 Har Krishan Bhalla & Sons.
Keywords: Achillea Phrygia; Antimicrobial Activity; Antioxidant Activity; Essential Oil